New Bachelards?: Reveries, Elements and Twenty-First Century Materialisms (Altre Modernità, 2012)
Recent years have seen an infusion of new ideas into material philosophy through the work of the so-called ‘new materialists’. Poignant examples appear within two recent books: the first, Vibrant Matter by Jane Bennett (2010), sets out to “enhance receptivity to the impersonal life that surrounds and infuses us” (2010: 4). The second, Elemental Philosophy by David Macauley (2010), advocates an anamnesis or recollection of the elements as imaginatively dynamic matter. Within his essays on the imagination of matter, Gaston Bachelard outlined an archetypal vision of the elements predicated upon the material imagination. He explored the manner in which the imagination inhabits the world, is triggered by the stimulus of material dynamism, and is formed from a co-constitution of subject and object. This article proposes that recent trends in materialist philosophy – as exemplified by the monographs of Bennett and Macauley – reinforce the ideas of Bachelard and take them in new directions. Bachelard provides us with a compelling argument for the rediscovery of material imagination, whereas New Materialism portrays a vision of matter filled with autonomous dynamism that lends itself to entering into a relationship with this imagination. Consequently, this article proposes that Gaston Bachelard has gained a new relevance as a result of contemporary trends in material philosophy, has taken on new possibilities through recent scholarship, and remains a force within the twenty-first century discursive landscape.
Keywords: Gaston Bachelard; Elemental Philosophy; Material Philosophy; Intellectual History; Comparative Analysis; James L. Smith